ByzRev 06.2024.077: Annie Montgomery Labatt, Byzantine Rome: (Past Imperfect). Leeds: ARC Humanities Press 2022. - Winterhager, Philipp (The Byzantine Review, 2024)
Annie Montgomery Labatt, Byzantine Rome (Past Imperfect). Leeds: ARC Humanities Press 2022. 212 S. – ISBN 978-1-64189-005-2